Emerging Pharmaceutical Pollutants in Wastewater and Their Effects on Aquatic Organisms - Al-Najjar , Mohammad A A (International Journal of Aquatic Research and Environmental Studies, 2026)
Pharmaceutical pollutants have gained increasing importance as contaminants of concern because they are biologically active substances that are not specifically removed in conventional wastewater treatment plants. Pharmaceuticals are discharged continuously from a range of sources such as municipal wastewater, hospitals, pharmaceutical manufacturing, livestock production, and aquaculture into aquatic ecosystems, where they remain at a range of concentrations from nanograms to micrograms per litre. While concentrations are generally low, pseudo-persistence is set up because of the continuous release, leading to prolonged exposure of aquatic organisms. Many studies have shown that pharmaceuticals can cause changes in fish behaviour, physiology, biochemistry, reproduction, and development in fish, invertebrates, algae, and microbial communities. Antibiotics also help to increase the spread of antimicrobial resistance genes, which have the potential to impact ecosystem functions and human health. This narrative review aims to summarize the key sources, environmental occurrence, fate, and ecotoxicological effects of pharmaceutical pollutants found in wastewater. Special focus is given to their impact on various trophic levels of aquatic ecosystems and the challenges associated with their elimination by traditional wastewater treatment processes. Lack of knowledge about chronic exposure, mixture toxicity, transformation products, and monitoring in developing countries is also pointed out. Therefore, the enhancement of wastewater treatment technologies, better environmental monitoring, and the establishment of comprehensive regulations play a crucial role in reducing pharmaceutical contamination and safeguarding water bodies.